A new record of species Asarum yunnanense T. Sugaw., Ogisu & C. Y. Cheng (Aristolochiaceae) for the flora of Vietnam - Tuan, Nguyen Anh; Thai, Tran Huy; Wang, Jenn-Che; Lu, Chang-Tse (Academia Journal of Biology, 2013)
There were 8 species of the genus Asarum previously recorded in Vietnam, this paper reported Asarum yunnanense T. Sugaw., Ogisu & C.Y. Cheng as a species newly recorded for the flora of Vietnam. This species was collected from Na Hang Nature reserve, Tuyen Quang province. Asarum yunnanense is characterized by the following features: herbs, rhizomes vertical, height 20-30 cm, 3-5 mm in diam., internodes 2-3 cm. Leaves paired, 1-2;  petiole 7-12 cm, villous; leaf blade adaxially deep geen with white speckles on veins, cordate-ovate, 9-11 × 16-18 cm, abaxial surface glabrous or pubescent on veins, adaxial surface sparsely hispid, base cordate, apex acute; cataphylls not seen. Peduncle declinate, 3.5 cm. Calyx slightly zygomorphic, purplish, campanulate; sepals connate beyond attachment to ovary, abaxially pilose, adaxially dark red pubescent; tube obconic; lobes spreading, triangular-orbicular. Stamens 12; filaments 0.3 mm, shoter than anthers; anthers 3 mm; connectives 0.8 mm, extended beyond anthers, subcylindric. Ovary inferior. Styles connate, short and thick, apex 6-cleft; stigmas white; stigmas terminal, radiating downward, decurrent. Fl. Nov-Dec.